2022
DOI: 10.1002/aenm.202201663
|View full text |Cite
|
Sign up to set email alerts
|

Excess PbI2 Management via Multimode Supramolecular Complex Engineering Enables High‐Performance Perovskite Solar Cells

Abstract: Excess PbI2 in perovskite film is an effective strategy for boosting perovskite solar cells (PSCs) performance. However, the presence of unreacted PbI2 is a critical source of intrinsic instability in perovskite under illumination, due to the photolysis of PbI2 (decomposed into metallic lead and iodine). Herein, this issue is solved by applying ionic liquids (ILs) on PSCs where the ILs can form types of stable supramolecules with residual lead iodide. The formation process and mechanism of the supramolecules a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
49
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(49 citation statements)
references
References 51 publications
0
49
0
Order By: Relevance
“…The carrier lifetime is longer for the control group perovskite film measured from the back side than that of the front side. According to the SEM diagram (Figure g,i and Figure S7) and GIWAXS results (Figure f) of the perovskite, this may be due to the excessive residual PbI 2 on the front-side surface of the control group perovskite (relative to the buried interface), which increases the trap density on the front-side surface. , The great improvement of the PL intensity and carrier lifetime on the back side of the perovskite treated with FAFa compared to the control group proves that the FAFa preplaced at the buried interface specifically inhibits the anion vacancy defects enriched at the buried interface.…”
Section: Resultsmentioning
confidence: 98%
“…The carrier lifetime is longer for the control group perovskite film measured from the back side than that of the front side. According to the SEM diagram (Figure g,i and Figure S7) and GIWAXS results (Figure f) of the perovskite, this may be due to the excessive residual PbI 2 on the front-side surface of the control group perovskite (relative to the buried interface), which increases the trap density on the front-side surface. , The great improvement of the PL intensity and carrier lifetime on the back side of the perovskite treated with FAFa compared to the control group proves that the FAFa preplaced at the buried interface specifically inhibits the anion vacancy defects enriched at the buried interface.…”
Section: Resultsmentioning
confidence: 98%
“…Reproduced with permission. [ 74 ] Copyright 2022, Wiley‐VCH. m) Stability of the control and [BMIM]Br‐treated devices (the statistical data of each condition are collected from five devices).…”
Section: Ionic Liquids For Interface Modificationmentioning
confidence: 99%
“…Ionic liquids (ILs) are a class of salt solutions composed by anions and cations, usually with the low melting point, high ionic conductivity, good chemical and thermal stability, and highly adjustable solubility . These unique properties of ILs have attracted great interests and applications in fuel cells, water electrolysis, and so on. In particular, ILs have been widely employed as surface modifiers of catalysts to regulate the surface properties and performance of electrocatalysts. For example, Li et al demonstrated the PtFeNi/ionic liquid conjugate system, which greatly enhanced the ORR activity and durability compared to the non-conjugated counterpart . The above inspiring works imply the great potential of ILs as the surface ligands to reveal the regularity between surface properties and electrocatalytic activity.…”
Section: Introductionmentioning
confidence: 99%